Restriction-Site-Associated DNA Sequencing Reveals a Cryptic Viburnum Species on the North American Coastal Plain. (6th December 2018) - Spriggs, Elizabeth L; Eaton, Deren A R; Sweeney, Patrick W; Schlutius, Caroline; Edwards, Erika J; Donoghue, Michael J
Abstract: Species are the starting point for most studies of ecology and evolution, but the proper circumscription of species can be extremely difficult in morphologically variable lineages, and there are still few convincing examples of molecularly informed species delimitation in plants. Here, we focus on the Viburnum nudum complex, a highly variable clade that is widely distributed in eastern North America. Taxonomic treatments have mostly divided this complex into northern ( V. nudum var. cassinoides ) and southern ( V. nudum var. nudum ) entities, but additional names have been proposed. We used multiple lines of evidence, including RADseq, morphological, and geographic data, to test how many independently evolving lineages exist within the V. nudum complex. Genetic clustering and phylogenetic methods revealed three distinct groups—one lineage that is highly divergent, and two others that are recently diverged and morphologically similar. A combination of evidence that includes reciprocal monophyly, lack of introgression, and discrete rather than continuous patterns of variation supports the recognition of all three lineages as separate species. These results identify a surprising case of cryptic diversity in which two broadly sympatric species have consistently been lumped in taxonomic treatments. The clarity of our findings is directly related to the dense sampling and high-quality genetic data in this study. We argue that there is a critical need for carefully sampled and integrative species delimitation studies to clarify species boundaries even in well-known plant lineages. Studies following the model that we have developed here are likely to identify many more cryptic lineages and will fundamentally improve our understanding of plant speciation and patterns of species richness.